Self-Medication Practices among College Students of Medical Technology, Derna, Libya: A Cross-Sectional Survey Based Study - Hafed Idris Zaatout; Reem Idris Zaatout (African Journal of Advanced Pure and Applied Sciences, 2023)
Self-medication is the practice of using medications to treat symptoms or illnesses that have been self-diagnosed without consulting a doctor. Despite its contribution to lessening the demand for medical services, it carries a number of health concerns for individuals who use it. Research on this subject revealed that students in the health sciences continued to self-medicate and advocate for it in public. Accordingly, the aim of this study was to estimate the prevalence of self-medication and investigate factors associated with it. A cross-sectional, questionnaire-based study was carried out to identify self-medication among undergraduate students at the College of Medical Technology, Derna, Libya. The data were collected and analyzed for counts and percentages. The study revealed that 64.72% of students reported self-medication practices in the preceding year. Moreover, self-medication practice was found more frequently in female students as compared to male students. Headache was the most frequently reported illness; commonly used drugs were antipyretics and analgesics; and the reason quoted was the disease’s ease of prevention and cure. This study shows that self-medication is widely practiced among college students. There is a dire need to make students aware of the pros and cons of self-medication in order to ensure safe usage of medicines